Ambiguous endings: Middle East regional security in the wake of the Arab Uprisings and the Syrian civil war - Helle Malmvig (Danish Institute for International Studies (DIIS), 2013)
Middle East regional security is changing rapidly. The Arab Uprisings and the Syrian civil war are changing not only the relationship between state and society, but also some of the region's core norms and historical divisions. This report analyses key changes in regional security in the Middle East since 2011 with emphasis on five important issues: * The relationship between state and society * Relationship with the West and foreign policy posturing * The impact of the Iran-Syria-Hezbollah resistance front and the radical-moderate divide * The Sunni-Shia rift and the rise of identity politics * The Saudi-Qatar rivalry and the role of the Muslim Brotherhood The report concludes that the Middle East regional security situation has not been as unstable and conflict-ridden since the 1950s and early 1960s, when revolutionary ideologies, interventionism and wars marked the region with equal force. To the extent that the Syrian civil war is allowed to carry on, this instability and level of conflict will continue to damage many of the positive developments originally set in motion by the Arab Uprisings, which is why a more robust, unified Western effort may called for.
Keywords: 300